Procedure for Handling 4-H Accounts: 4-H Financial Management - Marilyn N. Norman; Joy C. Jordan (EDIS)
4H5.1, a one-page factsheet by Marilyn N. Norman and Joy C. Jordan, introduces a series of factsheets designed to help 4-H leaders understand and correctly manage 4-H finances. Published by the UF Department of Family, Youth and Community Sciences, February 2007.